Pengaruh Persepsi pada Electronic Word of Mouth (e-WOM) melalui Beauty Vlogger dan Citra Merek terhadap Minat Beli Produk Catrice - Rania Fatma Razany; Sri Widowati Herieningsih (Interaksi Online, 2018)
This research is motivated by the increasing of cosmetic enthusiasts today and the number of beauty products that are able to meet those needs. From many cosmetic products available, Catrice is a new product that must be able to compete with earlier products in Indonesia. One of the marketing strategies of the company is through a beauty vlogger that is able to shape the perception of the product and must build its brand image. This study aims to determine whether there is influence between the perception of electronic word of mouth (e-WOM) through beauty vlogger and brand image toward the purchase intention of Catrice product. This research is an explanatory research with this research object are women arround 17-40 years who watch Catrice One Brand Tutorial-2 video by Suhay Salim. The results showed that there is a very strong influence between the perception of electronic word of mouth (e-WOM) through beauty vlogger toward purchase intention of Catrice product with 0,000 significance level and 0,739 regression coefficient. This means that the higher perception of electronic word of mouth (e-WOM) through the beauty vlogger the higher purchase intention of Catrice products. In the second hypothesis shows there is a strong influence between brand image with Catrice product purchase intention with a significance value of 0,000 and a regression coefficient of 0.337. This means that the higher brand image the higher purchase intention of Catrice products. For further research it is hoped that the researcher can study more about other factors that can influence purchase intention such as product promotion.